Reinforcing Health Data Sharing through Data Democratization - Wang, Yuhang; Blobel, Bernd; Yang, Bian (Journal of personalized medicine, 2022)
In this paper, we propose a health data sharing infrastructure which aims to empower a democratic health data sharing ecosystem. Our project, named Health Democratization (HD), aims at enabling seamless mobility of health data across trust boundaries through addressing structural and functional challenges of its underlying infrastructure with the core concept of data democratization. A programmatic design of an HD platform was elaborated, followed by an introduction of one of our critical designs-a "reverse onus" mechanism that aims to incentivize creditable data accessing behaviors. This scheme shows a promising prospect of enabling a democratic health data-sharing platform.
Keywords: eHealth; data democratization; health data infrastructure; privacy-enhancing technologies